Effects of drought hardening on the carbohydrate dynamics of Quercus acutissima seedlings under successional drought - Li, Qiang; Liu, Xiao; Sun, Xinke; Zhao, Mingming; Liu, Lele; Wang, Ning; Gao, Qun; Fan, Peixian; Du, Ning; Wang, Hui; Wang, Renqing (Frontiers in Plant Science, 2023)
As precipitation patterns are predicted to become increasingly erratic, the functional maintenance of warm-temperate forests constitutes a key challenge for forest managers. In this study, two-year-old Quercus acutissima seedlings were selected to elucidate the mechanisms whereby they respond to soil water fluctuations and the drought hardening effects on plant carbohydrate dynamics. Seedlings were trained under different soil water conditions for two months: drought (D), well-watered (W), one-month drought and then one-month well-watered (D-W), and one-month well-watered and then one-month drought (W-D). The functional traits involved in water-and carbon-use strategies were explored at the end of the hardening period.Compared to seedlings in group W, seedlings in groups D, D-W, and W-D had increased potential for carbon uptake (i.e., light saturated point, maximum RuBP saturated rate, and electron transport rate) and water uptake (i.e., fine root to coarse root ratio) and downregulated growth and mitochondrial respiration to decrease carbon consumption. After water fluctuation hardening, we performed a successional dry-down experiment for one month to detect carbohydrate dynamics and explore the acclimation caused by prior hardening. Our results revealed that there were more soluble sugars allocated in the leaves and more starch allocated in the stems and roots of seedlings hardened in the D, W-D, and D-W treatments than in W seedlings. No significant changes in total non-structural carbohydrates were found. In addition, we found near-zero (seedlings trained by D, D-W treatments) or negative (seedlings trained by W-D treatment) growth of structural biomass at the end of the dry-down experiment, which was significantly lower than that of W-hardened seedlings. This suggests that there was a shift in allocation patterns between carbon storage and growth under recurrent soil drought, which can be strengthened by drought memory. We conclude that Q. acutissima seedlings adjusted waterand carbon-use strategies in response to water fluctuations, whereas stress memory can enhance their overall performance in reoccurring drought. Therefore, taking advantage of stress memory is a promising management strategy in forest nurseries, and drought-trained seedlings might be more suitable for afforestation practices in sites characterized by fluctuating soil water content, considering the ongoing global climatic changes.